Could the UK Foundation Programme training post allocation process result in regional variations in the knowledge and skills of Foundation doctors? A cross‐sectional study. Issue 4 (27th November 2020) - Beck, Christopher; Brown, Celia
Abstract: Background and Aims: The allocation of medical school graduates to Foundation Schools (post‐qualification training, organized at regional level) in the United Kingdom uses a ranking process that takes into account educational performance at medical school and performance on a situational judgment test (SJT). We aimed to compare the performance of United Kingdom graduates allocated to different United Kingdom Foundation School according to three metrics: educational performance measure (EPM), SJT, and prescribing safety assessment (PSA). Methods: We used a cross‐sectional study design using data from the UK Medical Education Database, studying 19 United Kingdom Foundation School groups. A total of 33 730 graduates from United Kingdom medical schools in the period 2014 to 2018 (inclusive) who started Foundation Training in August 2018 or earlier were included in the study, excluding those allocated to the Academic Foundation Programme or the Armed Forces Deanery. The outcomes were within‐year standardized mean scores (by Foundation School) on the EPM, SJT, and PSA. Results: There was a significant difference between Foundation Schools in the Educational Performance Measure ( F = 401, P < .001), SJT ( F = 213, P < .001), and PSA ( F = 95, P < .001). Tukey‐Kramer pairwise comparisons between Foundation Schools showed a very high percentage of statistical significance (78%, 402/513 comparisons). The Cohen's d effect size for the difference in means and Tukey‐Kramer 95% confidence intervals between the Foundation Schools with the highest (North West Thames) and lowest (West Midlands North) means were 1.92 (1.77‐2.07) for the EPM, 1.59 (1.44‐1.73) for the SJT, and 0.94 (0.79‐1.09) for the PSA. Conclusion: There is a statistically significant difference between the knowledge and skills of doctors (as measured by the three metrics used in this study) entering the Foundation Programme in different Foundation Schools. It is less clear whether this has an impact on patient care and thus is unfair from the perspective of the patient.